THE URINARY EXCRETION OF 5-HYDROXYINDOLE-ACETIC ACID IN PATIENTS WITH MENOPAUSAL FLUSHING - Rowell, N. R. (1960)
The 24-hour urinary excretion of 5-hydroxyindoleacetic acid in women with post-menopausal flushing attacks was compared with that of a control group of post-menopausal women without flushing attacks. The results were normal in the women with post-menopausal flushing, and it is concluded that 5-hydroxytryptamine is not a factor in the pathogenesis of post-menopausal flushing.